The detection dogs test is more sensitive than real-time PCR in screening for SARS-CoV-2 - Mohammed Hag-Ali (Nature Portfolio, 2021)
Hag-Ali and colleagues highlight the potential for using trained dogs for detecting COVID-19 positive patients. The dogs, originally trained for explosives detection, were able to detect COVID-19 positive sweat samples with a sensitivity rivaling the gold-standard RT-PCR test currently used.